Demonstrating In Situ Formation of Globular Microstructure for Thixotropic Printing of EN AW-4043 Aluminum Alloy - Silvia Marola; Maurizio Vedani (Metals)
This study explores the feasibility of generating a globular microstructure in situ during the thixotropic 3D printing of the EN AW-4043 alloy, starting from a conventional cold-rolled wire. Thermodynamic simulations using Thermo-Calc software were first conducted to identify the semi-solid processing window of the alloy, based on the evolution of liquid and solid fractions as a function of temperature. Guided by these results, thermal treatments were performed on cold-rolled wires to promote the formation of a globular microstructure. A laboratory-scale printing head prototype was then designed and built to test continuous heating and deposition conditions representative of a thixotropic additive manufacturing process. The results showed that a globular microstructure could be achieved in the cold-rolled EN AW-4043 wires by heating them at 590 °C for 5 min in a static muffle furnace. A similar effect was observed when continuously heating the wire while it flowed through the heated printing head. Preliminary deposition tests confirmed the viability of this approach and demonstrated that thixotropic 3D printing of EN AW-4043 alloy is achievable without the need for pre-globular feedstock.